From microbial upcycling to biology-oriented synthesis: combining whole-cell production and chemo-enzymatic functionalization for sustainable taxanoid delivery. Issue 23 (8th November 2018) - Hirte, M.; Mischko, W.; Kemper, K.; Röhrer, S.; Huber, C.; Fuchs, M.; Eisenreich, W.; Minceva, M.; Brück, T. B.
Abstract : Conversion of low-value, by-product streams into taxadiene in conjunction with new purification and processing options expanding the taxanoids' chemical space. Abstract : A holistic bio-process based on the microbial upcycling of low-value feedstocks and leading to chemo-enzymatically derived, functionalized taxanoids was established. The upcycling of biotechnological by-product streams glycerol and corn steep liquor by an engineered Escherichia coli strain that constitutively expressed bottleneck enzymes within the MEP-pathway led to the formation of 364.4 ± 10.7 mg L −1 taxadiene within 44 h. In contrast to standard inducible systems, our constitutive microbial production system provided concomitant growth and taxadiene formation. This strategy is the basis for subsequent continuous taxadiene production processes, which is favorable under economic constraints. The growth dependent taxadiene production showed improved yields, reproducibility and transferability at any scale compared to inducible taxadiene production platforms examined in this study. Additionally, we developed new taxadiene isolation and purification strategies. To that end, these new downstream processing strategies display efficient alternatives to conventional biphasic, in situ extraction and purification procedures. Specifically, we developed a rapid and easy two-step extraction procedure followed by centrifugal partition chromatography purification. This process strategy provided 249.0 ± 11.1 mg L −1 taxadiene with 95% purity from E. coli high cell-density cultures at a liter scale. To functionalize taxadiene, a mild lipase mediated epoxidation reaction was devised. Optimization of this biology-oriented synthesis strategy led to a quantitative conversion of taxadiene to taxa-4(5), 11(12)-bisepoxide with an enantiomeric excess of over 83%. The holistic process strategy afforded in excess of 215 mg taxa-4(5), 11(12)-bisepoxide by upcycling the low-value feedstocks glycerol (300 g) and corn steep liquor (25 g).